2022
DOI: 10.1165/rcmb.2021-0563oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Macrophages Encompass Transcriptionally and Functionally Distinct Subsets Altered by Smoking

Abstract: Alveolar macrophages (AMs) are functionally important innate cells involved in lung homeostasis and immunity and whose diversity in health and disease is a subject of intense investigations. Yet, it remains unclear to what extent conditions like smoking or chronic obstructive pulmonary disease (COPD) trigger changes in the AM compartment. Here, we aimed to explore heterogeneity of human AMs isolated from healthy nonsmokers, smokers without COPD, and smokers with COPD by analyzing BAL fluid cells by flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…On the basis of prior work in mice, the prevailing concept has been that AMs self-maintain with minimal contribution from blood monocytes during homeostasis ( 3 5 ). However, recent studies, including this one, suggest that monocytes contribute to the diversity of the AM pool ( 1 , 2 , 6 , 7 ). For example, Cluster 3 expressed both classical macrophage-associated genes in addition to monocyte-associated gene signatures.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…On the basis of prior work in mice, the prevailing concept has been that AMs self-maintain with minimal contribution from blood monocytes during homeostasis ( 3 5 ). However, recent studies, including this one, suggest that monocytes contribute to the diversity of the AM pool ( 1 , 2 , 6 , 7 ). For example, Cluster 3 expressed both classical macrophage-associated genes in addition to monocyte-associated gene signatures.…”
mentioning
confidence: 89%
“…In this issue of the Journal , Liégeois and colleagues (pp. 241–252 ) report on their examinations of the identity and heterogeneity of AMs comparing healthy nonsmokers, non-COPD smokers, and COPD smokers using a combination of approaches that include flow cytometry and bulk and single-cell RNA sequencing (scRNA-seq) of BAL cells ( 2 ) ( Figure 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in long-term inflammatory conditions, such as the causatives of COPD, macrophages promote persistent ECM degradation. For example, macrophages in bronchoalveolar lavage (BAL) of COPD smokers are more prone to degrade elastin than macrophages from healthy individuals due to increased MMP activity [ 56 , 64 ]. Accordingly, in several studies in humans and mice, MMPs, particularly macrophage-derived MMPs, have been associated with the pathogenesis of COPD.…”
Section: Mmps In Copdmentioning
confidence: 99%
“…In the acute phase of infection, IMs will be chemotactic to the alveoli cavity and recruited to become RecAMs ( 37 ). In addition, RNA gene sequencing showed that the immunoprogramming of RecAMs was dynamic ( 32 , 35 ) and could develop into the same phenotype and provide the same functionality as RAMs during the peak inflammatory periods ( 38 , 39 ), including the production of pro-inflammatory cytokines and elimination of pathogens. RecAMs release anti-inflammatory factors to repair pathologically damaged tissues when the inflammation is subsiding.…”
Section: Classification and Characteristics Of Amsmentioning
confidence: 99%